Effectiveness of diet refeeds and diet breaks as a precontest strategy - Escalante, G.; Campbell, B. I.; Norton, L. (Strength and Conditioning Journal, 2020)
Physique competitors focus on optimizing body composition through maximizing muscle mass and loss of body fat. Competitors frequently experiment with various methodologies purported to improve body composition, but often, there is a lack of evidence on their efficacy. Emerging evidence suggests that intermittent energy restriction (IER) methodologies such as refeeds and diet breaks may offer various benefits to competitors by improving fat loss efficiency, lean body mass retention, and attenuating metabolic adaptation to weight loss. This review examines these methodologies and the evidence for their efficacy and proposes practical ways to implement IER that may benefit physique competitors.